ANALISIS PENENTUAN TARIF KAMAR HOTEL DENGAN METODE ACTIVITY BASED COSTING: (Studi Kasus Pada Hotel Sylvia Maumere) - Aja, Theresia B; Djou, Laurentius D Gadi; Thalib, Sabra B Wahab (Program Studi Akuntansi Universitas Flores, 2020)
This study aims to determine the calculation of hotel room rates using the Activity Based Costing method and the comparison of the calculation of hotel room rates based on the traditional methods used by hotel management with Activity Based Costing. The research method used is quantitative descriptive analysis method. The data collection method used in this research is by using the observation method, the interview method, and the documentation method. The results of the calculation of room rental rates using the Activity Based Costing method approach, namely, for the Superior Twin room type of Rp. 216,648.77 for the Superior Double room type of Rp. 236,680.56 for the Superior Triple room type of Rp. 331,751.82 for the Deluxe room type of Rp. IDR 480,014.08 and for the Suite room type is IDR 3,016,106.64. There is a difference in room rental rates that are lower for the types of Superior Twin, Superior Double, and Superior Triple rooms from the calculation results of the Activity Based Costing method with the calculation of the company using the traditional method approach, namely Rp. 131,588.74, Rp. 111,886.26 and respectively. IDR 144,318.09. Meanwhile, the higher room rental rates using the Activity Based Costing method, namely the Deluxe and Suite types of Rp.75,944.17 and Rp.2,144,770.64.